John Donne's performances sermons, poems, letters and devotions - Fetzer, Margret (Manchester University Press, 2010)
This is a comparative reading of Donne's poetry and prose, which eschews questions of personal or religious sincerity in order to recreate an image of John Donne as a man of many performances.